Synchronous multiple primary squamous cell carcinoma a rare entity - Mathew, Anuna Laila; Joseph, Biju Baby; Deepa, M S; Premkumar, Preeja; Sunil, S (Indian Journal of Case Reports, 2020)
Second primary tumor (SPT)develops due to extensive initiation and promotion by various carcinogens such as tobacco and alcohol, leading to a widespread disorder of the epithelial maturation and differentiation with a field effect. Therefore, environmental factors which cause the development of the first tumor can probably cause the subsequent premalignant and malignant changes. This article describes an unusual case of metachronous multiple primary squamous cell carcinomas in the oral mucosa in a chronic smoker and alcoholic and also discusses the clinical features and outcome of SPT.